Edukasi Kesehatan Pendengaran Akibat Kebisingan Mesin Pada Karyawan Produksi PT. X di Kawasan Industri Cikarang - Pakpahan, Hotmaria Agustina; Evans, Guterus; Usman, Hadiyanto; Situmorang, Evi Ulina Margareta (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
Hearing loss and deafness are worldwide problems in both developed and developing countries. Noise from work equipment and the workplace environment is one of the physical factors that affect work safety. Disturbances caused by machine noise include hearing loss, communication loss and concentration loss. Company workers who use machines in carrying out their daily work are one of the high-risk populations for hearing loss and deafness. The aim of this activities was to carry out this educational activity to contribute and increasing knowledge of the importance of hearing health and to handle machine noise in the workplace. This community service activity involves lecturers and students in collaboration with the company and is carried out offline and attended by 159 employees. This activity was carried out in 2023, and education was provided in the form of presentations, interactive discussions and games. Measurement of respondents' knowledge was carried out using pre-test and post-test questionnaires. The results of the independent sample T-test showed an increase in the respondents' average knowledge score, from 6.58 to 7.02, with a p-value of 0.0005. This indicates that the hearing health education related to machine noise for production employees at PT X in the Cikarang Industrial Area, Bekasi, had a significant impact on improving participants' knowledge. The conclusion of this activities shows that there is an increase of employees knowledge before education (pre test) than knowledge after education (post test). Key words: education, employees, health, knowledge, hearing